God man för ensamkommande barn - krävs partsställning i LVU-mål? - Karlsson,Sonja (2016)
This essay aims to investigate the role of the guardian appointed to unaccompanied minors in Sweden, especially what role they have in cases of compulsory care. The essay defines unaccompanied minors and explores what regulations there are for them and investigates the role of the guardian compared to other representatives in Swedish law. The rights of the parties in the Swedish Care of Young Persons Act is examined. Finally, there is a discussion as to whether or not the guardians would need to obtain some rights in order to fulfil their mission, namely the right to request an oral hearing, the right to be called to the oral hearing, the right to their own legal representative and the right to appeal. The role of the guardian in general is very unclear. While they are guardians and custodians in one, this does not guarantee them all of the rights nor all of the obligations. The point of the essay is to shine a light on the issue as well as to argue about what the mission entails. To discover the guardians’ involvement today an investigation was made. Concerns both for and against giving the guardian the same rights as parents in cases of compulsory care are weighed against each other, after which the essay presents recommendations. These are that the guardian should be able to request an oral hearing and be called to it, and that the guardian should have the right to a legal representative if he or she has no legal knowledge and if the child is under the age of 15. The guardian already has the possibility to appeal all disadvantageous decisions on the child’s behalf. In conclusion, some guardians will need position as a party while the others will need the right to request an oral hearing and to be called to it. There are several changes being discussed due to the critique of the Swedish guardianship system for unaccompanied minors, the coming update of the Care of Young Persons Act as well as the possible incorporation of the UN Convention on the Rights of the Child into Swedish law.
Keywords: administrative procedure; public law; partsställning; LVU; god man för ensamkommande barn; god man; offentlig rätt; förvaltningsprocessrätt; guardian; guardian for unaccompanied minors; care of young persons act; position as party